Diagnóstico socio-económico ambiental del agua potable en el cantón Manta periodo 2013-2014 - Cañarte Parrales, Johanna María (2015)
This research aimed an environmental socioeconomic analysis of drinking water in Manta canton. The study was non experimental, the use of technological tools such as REDATAM for the determination of the population and the different supplying routes of drinking water. Data from the population are both from rural and urban areas were taken from the population and housing census 2010, through this software it was able to meet the economic activity of the population and their payment capacity; it was established that the people of low income being 22% develop activities of wholesale and retail in a canton identified as national and international tourism destination, followed by 15% of people working in the manufacturing sector and 8% work in construction denoting their low income so it can be difficult for them the payment of the service. That is why a proposal for the reconciliation of both parties and establishes payment agreements.